Respiratory tract infections at the Grand Magal de Touba: a seven-year study - Coumba Diouf; Ihssane Ouaddane; Van Thuan Hoang; Ndiaw Goumballa; Dame Ndiaye; Hubert Bassene; Masse Sambou; Philippe Gautret; Cheikh Sokhna (Scientific Reports)
Abstract The Grand Magal of Touba (GMT) is the largest religious gathering in West Africa, and, like any large mass gathering, presents a risk of transmission of infectious diseases, mainly respiratory tract infections. Respiratory pathogen carriage was assessed by qPCR between 2017 and 2023 in healthy and ill pilgrims. The study included 1067 pilgrims comprizing 328 healthy controls, 298 pilgrims with respiratory symptoms who did not consult and 441 patients who consulted for respiratory symptoms. Among healthy controls, 7% tested positive for rhinovirus, 4% for endemic coronaviruses, 45% for Haemophilus spp. and 29% for Staphylococcus aureus. Among non-consulting ill pilgrims, 14% tested positive for rhinovirus, 8% for endemic coronaviruses, 45% for Haemophilus spp., 31% for S. aureus and 32% for Streptococcus pneumoniae. Among consulting patients, 29% tested positive for influenza A, 14% for respiratory syncytial virus, 9% for rhinovirus, 62% for Haemophilus spp., 47% for S. pneumoniae and 39% for Moraxella catarrhalis. Co-infection with viruses and bacteria was 12% in healthy controls, 23% in non-consulting ill pilgrims and 51% in consulting patients. Female gender was independently associated with a higher risk for respiratory symptoms. Symptomatic individuals were 53 times more likely to test positive for influenza A virus, 2 times for S. pneumoniae and M. catarrhalis and 3 times more likely to have a bacteria-virus co-infection. When comparing non-consulting ill pilgrims and consulting patients, the latter were 29 times more likely to test positive for influenza B virus, 16 times for respiratory syncytial virus, 14 times for influenza A virus and 3 times for M. catarrhalis. Influenza virus, respiratory syncytial virus, S. pneumoniae and M. catarrhalis could play a major role in the pathogenesis of respiratory infections at the GMT.